Widespread prevalence of a methylation-dependent switch to activate an essential DNA damage response in bacteria. - Aditya Kamat; Ngat T Tran; Mohak Sharda; Neha Sontakke; Tung B K Le; Anjana Badrinarayanan (PLoS Biology)
DNA methylation plays central roles in diverse cellular processes, ranging from error-correction during replication to regulation of bacterial defense mechanisms. Nevertheless, certain aberrant methylation modifications can have lethal consequences. The mechanisms by which bacteria detect and respond to such damage remain incompletely understood. Here, we discover a highly conserved but previously uncharacterized transcription factor (Cada2), which orchestrates a methylation-dependent adaptive response in Caulobacter. This response operates independently of the SOS response, governs the expression of genes crucial for direct repair, and is essential for surviving methylation-induced damage. Our molecular investigation of Cada2 reveals a cysteine methylation-dependent posttranslational modification (PTM) and mode of action distinct from its Escherichia coli counterpart, a trait conserved across all bacteria harboring a Cada2-like homolog instead. Extending across the bacterial kingdom, our findings support the notion of divergence and coevolution of adaptive response transcription factors and their corresponding sequence-specific DNA motifs. Despite this diversity, the ubiquitous prevalence of adaptive response regulators underscores the significance of a transcriptional switch, mediated by methylation PTM, in driving a specific and essential bacterial DNA damage response.